Autogenous bone grafts in oral implantology-is it still a "gold standard"? A consecutive review of 279 patients with 456 clinical procedures - Andreas Sakkas; Frank Wilde; Marcus Heufelder; Karsten Winter; Alexander Schramm (SpringerOpen, 2017)
Abstract Background This study assessed the clinical outcomes of graft success rate and early implant survival rate after preprosthetic alveolar ridge reconstruction with autologous bone grafts. Methods A consecutive retrospective study was conducted on all patients who were treated at the military outpatient clinic of the Department of Oral and Plastic Maxillofacial Surgery at the military hospital in Ulm (Germany) in the years of 2009 until 2011 with autologous bone transplantation prior to secondary implant insertion. Intraoral donor sites (crista zygomatico-alveolaris, ramus mandible, symphysis mandible, and anterior sinus wall) and extraoral donor site (iliac crest) were used. A total of 279 patients underwent after a healing period of 3-5 months routinely computer tomography scans followed by virtual implant planning. The implants were inserted using guided oral implantation as described by Naziri et al. All records of all the consecutive patients were reviewed according to patient age, history of periodontitis, smoking status, jaw area and dental situation, augmentation method, intra- and postoperative surgical complications, and surgeon's qualifications. Evaluated was the augmentation surgical outcome regarding bone graft loss and early implant loss postoperatively at the time of prosthodontic restauration as well a follow-up period of 2 years after loading. Results A total of 279 patients underwent 456 autologous augmentation procedures in 546 edentulous areas. One hundred thirteen crista zygomatico-alveolaris grafts, 104 ramus mandible grafts, 11 symphysis grafts, 116 grafts from the anterior superior iliac crest, and 112 sinus lift augmentations with bone scrapes from the anterior facial wall had been performed. There was no drop out or loss of follow-up of any case that had been treated in our clinical center in this 3-year period. Four hundred thirty-six (95.6%) of the bone grafts healed successfully, and 20 grafts (4.4%) in 20 patients had been lost. Fourteen out of 20 patients with total graft failure were secondarily re-augmented, and six patients wished no further harvesting procedure. In the six patients, a partial graft resorption was detected at the time of implantation and additional simultaneous augmentation during implant insertion was necessary. No long-term nerve injury occurred. Five hundred twenty-five out of 546 initially planned implants in 259 patients could be inserted into successfully augmented areas, whereas 21 implants in 20 patients due to graft loss could not be inserted. A final rehabilitation as preplanned with dental implants was possible in 273 of the 279 patients. The early implant failure rate was 0.38% concerning two out of the 525 inserted implants which had to be removed before the prosthodontic restoration. Two implants after iliac crest augmentation were lost within a period of 2 years after loading, concerning a total implant survival rate after 2 years of occlusal loading rate of 99.6% after autologous bone augmentation prior to implant insertion. Conclusions This review demonstrates the predictability of autologous bone material in alveolar ridge reconstructions prior to implant insertion, independent from donor and recipient site including even autologous bone chips for sinus elevation. Due to the low harvesting morbidity of autologous bone grafts, the clinical results of our study indicate that autologous bone grafts still remain the "gold standard" in alveolar ridge augmentation prior to oral implantation.